Study of Effectiveness of Character Education at Primary Level in Islamabad - Usama Bashir; Anwar Ul Haq; Syed Ghazanfer Abbas (Jurnal Multidisiplin Madani, 2023)
The study was carried out to evaluate the effectiveness of character education for the development of basic values and to compare the difference in value development of students on the basis of gender. The study was experimental in nature and pretest posttest method was used in the study. The population of study comprises 39132 students of 355 primary schools at Islamabad. 25 students from the grade three of primary level were selected as the sample of the study. Two self-generated tools, pre and post observation and lesson plans were used for the experimental study. The experimental study was carried out for 4 weeks in primary level schools. Two teachers were detailed for teaching and assessment of students. Pre observation of selective group conducted before the experiment. It records the prior condition of values and character of students. Then experiment was conducted. 5 values were taught in 20 days. Total class duration of this experiment was 600 minutes. These minutes were distributed as 30 minutes as per day. After the experiment, post observation was conducted to measure the effect of character education and gander-based comparison in value development through character education. After analyzing the pre and post observation data through SPSS, it was found that character education affects the process of value development of students. SPSS calculated 8.78 differences between post and pre observation. The second finding was about the evaluation of gender-based comparison of value development through character education. The difference measured in pre observation was 0.85 and difference in post observation data was 0.29. This minor difference proved that there was no gender difference in value development through character education. According to findings it is recommended that organizations and institutions may integrate character education in the prescribed curriculum. They may offer special diplomas and short courses of character education